Purification and Biochemical Characterization of Three Myotoxins from Bothrops mattogrossensis Snake Venom with Toxicity against Leishmania and Tumor Cells. (3rd March 2014) - Moura, Andréa A. de; Kayano, Anderson M.; Oliveira, George A.; Setúbal, Sulamita S.; Ribeiro, João G.; Barros, Neuza B.; Nicolete, Roberto; Moura, Laura A.; Fuly, Andre L.; Nomizo, Auro; da Silva, Saulo L.; Fernandes, Carla F. C.; et al.
Abstract : Bothrops mattogrossensis snake is widely distributed throughout eastern South America and is responsible for snakebites in this region. This paper reports the purification and biochemical characterization of three new phospholipases A2 (PLA2 s), one of which is presumably an enzymatically active Asp49 and two are very likely enzymatically inactive Lys49 PLA2 homologues. The purification was obtained after two chromatographic steps on ion exchange and reverse phase column. The 2D SDS-PAGE analysis revealed that the proteins have pI values around 10, are each made of a single chain, and have molecular masses near 13 kDa, which was confirmed by MALDI-TOF mass spectrometry. The N-terminal similarity analysis of the sequences showed that the proteins are highly homologous with other Lys49 and Asp49 PLA2 s from Bothrops species. The PLA2 s isolated were named BmatTX-I (Lys49 PLA2 -like), BmatTX-II (Lys49 PLA2 -like), and BmatTX-III (Asp49 PLA2 ). The PLA2 s induced cytokine release from mouse neutrophils and showed cytotoxicity towards JURKAT (leukemia T) and SK-BR-3 (breast adenocarcinoma) cell lines and promastigote forms of Leishmania amazonensis . The structural and functional elucidation of snake venoms components may contribute to a better understanding of the mechanism of action of these proteins during envenomation and their potential pharmacological and therapeutic applications.